From Value Co-creation to positive experiences and customer satisfaction. A customer perspective in the hotel industry - Solakis, Konstantinos; Peña-Vinces, Jesús; Lopez-Bonilla, Jesús M.; Aguado, Luis F. (Technological and Economic Development of Economy, 2021)
This study evaluates whether the Value Co-creation (VCC) process in hotels contributes to positive guest experience and satisfaction. This paper utilizes the DART model (Dialogue, Access, Risk, and Transparency) as the main framework to explore VCC in hotels. This research is the first to both adjust the DART model to a customer’s viewpoint and evaluate it in the hotel context. The included data is derived from 484 international tourists lodged in Greek hotels and is analyzed with the structural equation modeling technique. Results suggest that the Dialogue component of DART does not affect the positive experience, while Access, Transparency, and Risk Assessment do, in fact, strongly influence tourist satisfaction. The current study enriches and consolidates VCC–DART theory in the hotel context.